The Effect of Tablet Fe on Improvement Hemoglobin in Adolescent Women Region Mining Morosi District - Muliasari, Indri; Sunarsih, Sunarsih; Nurmiaty, Nurmiaty (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: Anemia is one of the nutritional problems in adolescents, especially at the Morosi Health Center with a prevalence of anemia in June 2022 of 27.95% who have an Hb of 9-10 g/dl, 9.67% have a Hb of 7-8 g/dl and 1.07% Hb< 7 g/dl. The purpose of this study was to determine the effect of giving Fe tablets to increase hemoglobin in young women in the mining area of Morosi District. Methods: This type of research is pre-experimental, with a one-group pre-test-post-test design. The population is part of young women in WonuaMorini Village, Besu Village, and Mendikonu Village, amounting to 72 people taken using the Proporsionatestratifed random Sampling technique. Hb level data was obtained by easy touch meter. The data were analyzed using the Wilcoxon sign rank test. Results: Showed the average Hb level before intervention was 11,38 g/dl and after intervention was 11,38 g/dl. The second week 11,68 g/dl after the intervention. The third week after the intervention was 12.86 g/dl and the fourth week after the intervention was 12.86 g/dl.The results of the Wilcoxon sign rank test obtained a p-value (0.000) < (0.05). Conclusion: There is no effect of giving Fe tablets in the first and there was an effect of giving Fe tablets in the Second to fourth weeks of increasing hemoglobin in young women in the mining area of ​​Morosi District. Research suggests that young women routinely consume blood-added tablets once a week.